ANNUAL CHANGES IN MAY RAINFALL AS AN INDEX TO WILD TURKEY HARVEST - Steven D. Roberts; William F. Porter (Wildlife Society Bulletin)
Abstract: Mortality associated with fall hunting of wild turkeys (Meleagris gallopavo) may be additive; thus, periodic monitoring of population trends is essential to effective management of wild turkey populations. Brood surveys are often used to assess population trends, but these surveys can be costly and data may be obtained after regulatory deadlines. We used linear regression analysis to examine the relation between May precipitation and reported fall harvest of wild turkeys in southwestern New York during 1972–95. The loge of the annual rate‐of‐change in May precipitation was associated negatively with the annual rate‐of‐change in harvest (P < 0.0001). Our data suggest that weather‐based indices can be a viable alternative to brood surveys. Our simple linear regression model correctly predicted the observed annual changes (increase vs. decrease) in fall harvest for 22 of 28 years. During 1987–99, this model yielded correct predictions of increased or decreased fall harvests for 11 of 12 years. Our data indicate that annual variation in nest success may be driving annual changes in New York's wild turkey population.